Spinal deformity in the adolescent athlete - Wood, K. B. (Clinics in Sports Medicine, 2002)
Today more and more children with diagnoses of adolescent spinal deformity are participating in athletic competitions. Certain sports appear to have an increased association with spinal deformity, especially in the adolescent female population. Modern treatment techniques including bracing will allow participation in most athletic endeavors. Those treated with surgery need to have their postoperative care individualized. However, modern surgical techniques still allow continued participation in most activities.